Bricks and mortar of well-being: exploring the housing-health connection - Roshanak Mehdipanah; Lara C. Weinstein (BMC, 2023)
Abstract Housing is a determinant of health. Increasing housing costs and worsening housing conditions have impacted populations worldwide. This Editorial aims to examine the dynamic connection between housing and health and the role of public health in addressing this relationship for a Collection launched at BMC Public Health on Housing as a determinant of health and well-being.